Rapid production of organic fertilizer from degradable waste by thermochemical processing - C. R. Sudharmaidevi; K. C. M. Thampatti; N. Saifudeen (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Chemical decomposition was studied as a potential method for the rapid conversion of waste to organic fertilizer. Methods Chemicals were screened, and process parameters were optimized. The physicochemical properties, phytotoxicity, and manurial efficiency of the product were assessed. A prototype machine was fabricated for the operation. Results Chemical treatment of ground fresh waste with HCl (0.25 N, 50 ml kg-1 ) for 30 min followed by KOH (0.5 N,100 ml kg-1 ) for 30 min at 100 C, and ambient pressure yielded a product that could be used in place of conventional organic manure. Only 8â14 h were required to complete the entire process. No by-product or leachate was produced. The quality of the product was comparable to that of conventional composts, except for the absence of microorganisms. The fortified organic fertilizer enhanced the yield of vegetables in pot trials. The process and the prototype machine were found beneficial by a public evaluation. Conclusions The new thermochemical waste processing method provides a quick and sustainable solution for hygienic waste disposal and the production of organic fertilizer.